2019
DOI: 10.1111/risa.13323
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Chemical Mixture Risk Assessment—Linking Data from Population‐Based Epidemiology and Experimental Animal Tests

Abstract: Humans are continuously exposed to chemicals with suspected or proven endocrine disrupting chemicals (EDCs). Risk management of EDCs presents a major unmet challenge because the available data for adverse health effects are generated by examining one compound at a time, whereas real-life exposures are to mixtures of chemicals. In this work, we integrate epidemiological and experimental evidence toward a whole mixture strategy for risk assessment. To illustrate, we conduct the following four steps in a case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…An interesting proposal by Bornehag et al (2019) suggests that exposure mixtures should first be identified and reconstructed based on evidence from epidemiological and biomonitoring data (Bornehag et al 2019). These mixtures can then be tested with in vivo experiments to determine a point of departure associated with the studied adverse health outcome, and the final step is to compare the similarity of the experimental data with outcomes measured in the human population (Bornehag et al 2019). In addition to taking into account mixtures in the risk assessment process, this approach could enable the systematic integration of epidemiological and experimental evidence (Bornehag et al 2019).…”
Section: Chemical Mixtures-something From Nothing?mentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting proposal by Bornehag et al (2019) suggests that exposure mixtures should first be identified and reconstructed based on evidence from epidemiological and biomonitoring data (Bornehag et al 2019). These mixtures can then be tested with in vivo experiments to determine a point of departure associated with the studied adverse health outcome, and the final step is to compare the similarity of the experimental data with outcomes measured in the human population (Bornehag et al 2019). In addition to taking into account mixtures in the risk assessment process, this approach could enable the systematic integration of epidemiological and experimental evidence (Bornehag et al 2019).…”
Section: Chemical Mixtures-something From Nothing?mentioning
confidence: 99%
“…These mixtures can then be tested with in vivo experiments to determine a point of departure associated with the studied adverse health outcome, and the final step is to compare the similarity of the experimental data with outcomes measured in the human population (Bornehag et al 2019). In addition to taking into account mixtures in the risk assessment process, this approach could enable the systematic integration of epidemiological and experimental evidence (Bornehag et al 2019). We note that with this proposed notion, the mechanistic effects of combinations of chemicals-whether independent, additive, or synergistic-are not a primary concern; the main concern is that these mixtures are relevant based on epidemiological and biomonitoring data.…”
Section: Chemical Mixtures-something From Nothing?mentioning
confidence: 99%
See 1 more Smart Citation
“…At gestational week 10, urine and serum were collected from the women and analyzed for 20 chemicals, including phthalates, phenols, and perfluorinated compounds. Using weighted quantile sum (WQS) regression, levels of 4 phthalate monoesters in the urine of 198 mothers were associated with shorter anogenital distance (AGD) in their baby boys at 21 months of age (Bornehag et al 2019). A mixture (Mixture S) was established for these four phthalates, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A mixture (Mixture S) was established for these four phthalates, i.e. monobutyl phthalate, monoisononyl phthalate, monoethylhexyl phthalate, and monobenzyl phthalate, with mixing proportions based on geometric means of estimated serum concentrations in the SELMA mothers (Bornehag et al 2019). Gestational exposure to Mixture S in mice led to reduced AGD and gonadal weight, histological changes in the gonads, and altered mRNA expression of regulators of steroidogenesis in the offspring (Repouskou et al 2019).…”
Section: Introductionmentioning
confidence: 99%